PERAN BAITUL ARQAM MUHAMMADIYAH DALAM MEMBANGUN KARAKTER BERBASIS NILAI-NILAI ISLAM BERKEMAJUAN - Hastuti, Putri (Anatesa : Kajian Pendidikan, Sosial dan Keagamaan, 2025)
Baitul Arqam is one of the cadre development programs within Muhammadiyah which aims to form individuals with strong and visionary Islamic personalities. This Baitul Arqam activity also instills an understanding of Muhammadiyah ideology, strengthens self-identity in developing Muhammadiyah business charities and associations. So, efforts and processes need to be made to instill awareness of the importance of understanding Islam as a religion that is always appropriate and appropriate in providing benefits to humans in ever-changing times. In every era there are always people or groups who call for improvement (ishlah) or renewal (tajdid) in the lives of Muslims. Therefore, Muhammadiyah is here to carry out this mission. Muhammadiyah places Islam as a foothold, guidance and spirit in pursuing the changes realized by Muhammadiyah in the form of thought, movement and service. Thus, Baitul Arqam activities are designed as an effort to build character based on progressive Islamic values, which is one of the characteristics of Muhammadiyah in responding to the dynamics of modern life. With Progressive Islam, Muhammadiyah seeks to dismantle the attitudes that shackle the understanding of Islam in a narrow view that is anti-change.